Pendidikan Islam dalam Sistem Pendidikan Nasional - Jannah, Fathul (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2013)
Islamic educationis an integral part of the National Education System. As part of the national educational system, Islamic education gets legitimacy to exist and get a place to live and thrive in Indonesia to meet need of education for Muslims. Accommodation to the Islamic education system and make the system of Islamic education institutions have a strong foundation to be developed with the support of funds and attention from the state. Therefore, the state is obliged to develop Islamic educational system as a kind of religious education in the national education system. In the system of national education, Islamic education as a system of religious education is carried out in different lines of formal, informal and non-formal.